O ensino de literatura na Educação Básica: da crise da perspectiva tradicional ao desenvolvimento de novos paradigmas metodológicos - Marta Aguiar; Lívia Suassuna (Universidade do Estado do Rio Grande do Norte, 2013)
This theoretical article is one part of our dissertation in Education by UFPE, more specifically one that addresses the teaching of Literature in Basic Education. First, we present the context for the criticism of the historicist paradigm, which led to valorize a teaching model concerned with the formation of the reader of literary texts. Then, we discuss in more detail the methodological proposals of Bordini and Aguiar (1993), for its strong influence in the 1990s and for the significant considerations it brings to the teaching of literature, and of Cosson (2006) and Cosson and Paulino (2009), due to space the discussion around the idea of literary literacy is gaining at the beginning of the XXI century. Our study also seeks to reflect on the contributions of Literary Theory for teaching in basic education, because to build a methodological approach to the teaching of any subject we can not disregard the collaboration of the theoretical field.